1986
DOI: 10.1136/hrt.56.6.509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the specific thromboxane receptor blocking drug AH23848 in patients with angina pectoris.

Abstract: HertfordshireSUMMARY The effect of the specific thromboxane receptor blocking drug AH23848 was investigated in two double blind placebo controlled studies in male patients with exercise induced angina pectoris and angiographically verified coronary lesions. In the first study cardiac pacing was performed in twenty patients after coronary angiography. Patients were then randomised into two groups and received either AH23848 (70 mg orally) or placebo. One hour later cardiac pacing was repeated. Neither treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Although aorto-bifemoral grafts rarely occlude, the important finding of a reduction in platelet interaction with prosthetic grafts warrants the testing of thromboxane receptor blocking drugs in maintaining patency under conditions of low flow, high resistance, such as found in femoropopliteal or aorta-coronary bypass grafts and where thrombosis represents a major problem (40)(41)(42). Thromboxane receptor blocking drugs such as AH23848 and the recently described compound GR32191 (43)(44)(45) have to date, proved free of serious adverse effects (25,26,46). Such drugs may therefore prove to have wide indications throughout arterial thrombo-embolic disease and great potential in arterial bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although aorto-bifemoral grafts rarely occlude, the important finding of a reduction in platelet interaction with prosthetic grafts warrants the testing of thromboxane receptor blocking drugs in maintaining patency under conditions of low flow, high resistance, such as found in femoropopliteal or aorta-coronary bypass grafts and where thrombosis represents a major problem (40)(41)(42). Thromboxane receptor blocking drugs such as AH23848 and the recently described compound GR32191 (43)(44)(45) have to date, proved free of serious adverse effects (25,26,46). Such drugs may therefore prove to have wide indications throughout arterial thrombo-embolic disease and great potential in arterial bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…TXA2-receptor blockade may be of potential therapeutic benefit in some forms of angina pectoris. Experimental and clinical studies have shown mixed results for TXA2 synthetase or receptor antagonists in angina (6,12,13,22), but the present study indicates further investigations in this area are warranted.…”
Section: Discussionmentioning
confidence: 51%
“…Studies by Lewy et al (16), have indicated that TXAz is produced rapidly in patients with angina pectoris who were subjected to atrial pacing, thus suggesting a role for TXA2 in angina pectoris. Early clinical trials with TXA2 synthetase inhibitors and receptor antagonists have given mixed results (6,13). A study by Hoeft et al (12) has indicated that inhibition of TXA2 synthesis appears to reduce severity of ischemia in a model of transient ischemia, though again, possible alterations in production of other arachidonic acid metabolites may cloud interpretation of the results.…”
Section: Introductionmentioning
confidence: 97%